Learner perceptions of gender representation in EFL grammar books - Lewandowski, Marcin (Lingua Posnaniensis, 2014)
It seems that there are very few research themes in sociolinguistics that have been as thoroughly explored as gender representation in educational materials (notably in E FL textbooks). However, relatively little attention has been paid to how learners themselves perceive the images of men and women in teaching resources. T he present contribution has been written in an attempt to fill this gap. Drawing on the findings of two small-scale survey studies conducted among Polish university students, it addresses two major issues. T he first one concerns the extent to which the choice of male or female-gendered sentence subjects in E FL grammar course books matches the learners’ associations and expectations. The other one, focusing specifically on attitudes to gender representation, seeks to demonstrate how the students view the ways male and female characters are portrayed in constructed examples of usage and practice sentences from English grammar textbooks. Both studies provide some indications of how E FL learners’ needs and expectations can be better addressed in teaching materials